Marker Assisted Screening of Nepalese rice for bacterial leaf blight (BLB) resistance - Amgai, Resham Babu; Niroula, Raj Kumar; Pantha, Sumitra; Hamal, Shreya Singh; Tamang, Bishal Gole; Sah, Bindeshwar Prasad; Bhatta, Madan Raj (Nepal Journal of Biotechnology, 2015)
Bacterial Leaf Blight (BLB) is the most important yield limiting factor in Nepalese rice. BLB resistance rice varieties are highly demanding in the country. Breeding efforts for developing disease resistant depends on availability and use of resistant gene donors. Nepalese rice landraces could be the source of resistant gene. Therefore, ninety six Nepalese rice accessions were screened using eight Simple Sequence Repeats (SSR) markers and one Sequence Tagged Sites (STS) marker for presence and absence of BLB resistance gene. We have detected BLB resistance gene Xa-10 on five accessions, Xa-13 on six accessions, Xa-7 on 23 accessions, Xa-3 and Xa-4 on 52 accessions, Xa-5 on 25 accessions, Xa-8 on 30 rice accessions. No any rice accessions tested have Xa-21. Similarly, 17 rice accessions showed three and more than three BLB resistance genes. Presence of Xa-13 on susceptible check variety CNTRL-85033 confirmed that this resistant gene is not working in Nepalese rice field. Therefore, Nepal need to pyramide the BLB resistant genes for durable resistance. Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 35-39